Demographic Rise Effect on Water Supply Systems in Urban Higher Learning Institutions; Case Study of Kenyatta University - Mary Makokha (Program Pascasarjana Universitas Sriwijaya, 2019)
In the past ten years, public institutions including Kenyatta University have experienced a surge in population growth, exacerbated by a demand for higher education. The university population has increased eight times more between the year 2006-2016 leading to inadequacy in accommodation services within university premises, thus three quarters of these students reside in the neighboring areas. This study aimed at looking at the impact of this population increase on the water systems. Quantitative and qualitative methods were employed; three FGDs, key informant interviews and 220 respondents were interviewed comprising of; students, households, caretakers and small business owners. The study established that 62% of the residents used water from municipal water integrated to borehole supply. There were high water shortages marked with rationing as supply was only 2-3 times a week during student peak sessions. Most residents reverted to boreholes that were sunk without following set standards. 60% stored water in locally made tanks with low storage capacity inadequate to meet demand. The respondents felt the need to have an integrated holistic approach and coordination among all relevant stakeholders including; government, management institutions, households, students, public institution administrators, and businesses in order to comprehensively manage the water resources effectively